2001
DOI: 10.1007/s004250000390
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of a vacuolar aquaporin in young and mature leaf tissues of Brassica napus in relation to water fluxes

Abstract: Recently, it has been shown that water fluxes across biological membranes occur not only through the lipid bilayer but also through specialized water-conducting proteins, the so called aquaporins. In the present study, we investigated in young and mature leaves of Brassica napus L. the expression and localization of a vacuolar aquaporin homologous to radish gamma-tonoplast intrinsic protein/vacuolar-membrane integral protein of 23 kDa (TIP/VM 23). In-situ hybridization showed that these tonoplast aquaporins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…TIPs represent a group of aquaporin homologues in plants, which are expressed in vacuolar membranes [28]. Recently, AtTIP2;1 expression in Arabidopsis roots was shown to be upregulated in response to nitrogen starvation [29].…”
Section: Resultsmentioning
confidence: 99%
“…TIPs represent a group of aquaporin homologues in plants, which are expressed in vacuolar membranes [28]. Recently, AtTIP2;1 expression in Arabidopsis roots was shown to be upregulated in response to nitrogen starvation [29].…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was carried out using antibodies for TIP [34], PIP [35] and LHCb3 (Agrisera AB, Sweden). Secondary antibodies (anti-rabbit or anti-chicken, coupled to alkaline phosphatase …”
Section: Western Blottingmentioning
confidence: 99%
“…A study of the distribution of PIP1 and TIP1 homologous proteins in leaves of Brassica napus showed that both types of protein were present in phloem elements of the minor veins but at a much lower level than in parenchyma cells of mesophyll and vascular bundles (Frangne et al, 2001). In phloem sap of barley transcripts of the PIP1 member emip have been detected (Doering-Saad et al, 2002).…”
Section: Aquaporins and The Water Relations Of Developing Seedsmentioning
confidence: 99%